Malaysia and the developing world : the Asian tiger on the Cinnamon Road - Stark, Jan (London : Routledge, 2013)
'As Malaysia's economy grows and flourishes, strong new links are being forged with other developing countries in the region and beyond. This book examines these new links. It argues that as many countries with which Malaysia has new links are Indian Ocean countries, many of them Muslim countries, a new style trading network is being formed, a network with Islamic characteristics, which echoes Indian Ocean Islamic trading networks of earlier times'--Publisher's description.
Includes bibliographical references and index.
Keywords: Malaysia -- Foreign relations -- Developing countries; Developing countries -- Foreign relations -- Malaysia; Malaysia -- Foreign relations -- Islamic countries; Islamic countries -- Foreign relations -- Malaysia